(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2008)
Analyzing the individual and group characters, the general ecological and biological peculiarities of the rare plant species small populations at high mountain zone of the Ukrainian Carpathians are formulated. The indicator characters to evaluate their viability are determined. The genetic variability, effective and general number, habitat area, number dynamic, especially for flowering individuals; efficiency of seed and vegetative reproduction; intrapopulation variability; vitality, variability and duration of individual ontogeny; mutual effect of neighbouring species are the most important. The aspects of the ecological structure of the small populations of different life forms species at nature conditions and under the anthropogenic factors are given.